Evaluation of Physical Egg Quality Parameters of Commercial Brown Laying Hens Housed in Five Production Systems - Benjamin N. Alig; Ramon D. Malheiros; Kenneth E. Anderson (Animals, 2023)
This study evaluates the effect of housing environment on the egg quality characteristics of brown egg layers as many different environments are currently used in the industry. Battery cages, barren colony cages, enriched colony cages, cage-free, and free-range environments were evaluated. Overall, all egg quality measurements were affected by housing environment (p < 0.01) except for vitelline membrane strength, elasticity, and egg solids. Eggshells and yolks were lightest in barren colony cages and darkest from free-range hens (p < 0.0001). Free-range eggs were heavier than eggs from all other environments (p < 0.0001). Cage-free eggs had lower albumen height and Haugh units than other environments (p < 0.0001). Lastly, cage-free and free-range eggs had stronger eggshells than the other environments (p < 0.0001), and free-range eggs had more elastic eggshells than eggs from conventional battery cages and barren colony cages (p < 0.01). Access to the range seemed to give free-range hens different nutritional advantages, which allowed for the darker yolks and shells. Furthermore, eggs from barren colony cages seemed to exhibit more negative characteristics. Simply adding enrichments to colony cages did not improve or detract from egg quality. From this research, it appears that, as the industry moves toward extensive environments, the egg quality of brown egg layers will improve.